PEMIKIRAN PROGRESIF MUHAMMAD ASAD TENTANG HADIS - Nabil, Ahmad Amir; Mohd. Marzuki, Zunaidah (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2021)
Makalah ini menyorot pemikiran hadis Muhammad Asad (1990-1992) yang dinilai progresif serta kontribusinya dalam pemahaman hadis kontemporer. Ia membincangkan pemahaman inti tentang hadis yang dirumuskan dalam karya-karyanya seperti Sahih al-Bukhari The Early Years of Islam; Islam at The Crossroads (bab “Hadis and Sunnah” dan “The Spirit of the Sunnah”); This Law of Ours and Other Essays; The Road to Mecca dan The Message of the Qur’an. Pengaruh hadis ini turut ditinjau dari artikelnya dalam jurnal Arafat dan makalahnya yang lain terkait tema-tema hadis dan sunnah, serta pemahaman serta tantangannya di abad modern, seperti tulisannya “Social and Cultural Realities of the Sunnah”. Bentuk kajian ini adalah bersifat deskriptif, analitis, historis dan komparatif. Kajian ini mencoba mengembangkan ide dan pemahaman hadis yang dirumuskan Asad dari perspektifnya yang modern dan membandingkannya dengan pemikiran-pemikiran sejarah yang krusial terkait prinsip hadis yang dibawakan oleh pemikir Islam yang lain. Hasil kajian ini menyimpulkan bahwa Muhammad Asad telah memberikan sumbangan yang penting dalam pemikiran hadis di abad modern dengan hasil penulisannya yang prolifik dan substantif, termasuk terjemahan dan syarahannya yang ekstensif terhadap Sahih al-Bukhari yang memuat komentar-komentar baru dan analisis sejarahnya yang mendalam terhadap kitab ini. Ia merumuskan pertentangan-pertentangan hukum dan istinbat-istinbat fuqaha’ dan muhaddith dalam tradisi syarah hadis yang kritis. Ia turut merespon pertikaian-pertikaian dasar yang dibangkitkan oleh golongan orientalis dan intelektual yang skeptis terhadap riwayat-riwayat sejarah dalam tradisi hadis.[Muhammad Asad's Progressive Thoughts on Hadith.The paper analyses the ideas of hadith (prophetic tradition) as espoused by Muhammad Asad (1990-1992) and its significance in contemporary hadith thought. It studies the essential ideas he developed in his discussion of hadith as reflected in his works such as Sahih al-Bukhari The Early Years of Islam; Islam at The Crossroads (chapter “Hadith and Sunnah” and “The Spirit of the Sunnah”); This Law of Ours and Other Essays, The Road to Mecca and The Message of the Qur’an. The influence of hadith was also deeply manifested in his “journalistic monologue” Arafat: A Monthly Critique of Muslim Thought, a periodical he founded in 1946 in Kashmir and other works that addresses significance principles and issues of hadith and essays that incorporate rising themes in contemporary ages, such as “Social and Cultural Realities of the Sunnah”. The research was structured based on descriptive, analytical, historical and comparative method. It attempts to analyse the crucial ideas of hadith principles brought forth by Asad and compared these with other critical views set forth of classical Muslim traditionists. The study concluded that Muhammad Asad had significantly contributed to the revival and development of hadith in the modern world with his profound translation and commentary of al-Bukhari’s Sahih – Sahih al-Bukhari The Early Years of Islam - that extensively survey the significant tradition of hadith and its intellectual and historical manifestation over centuries. He also responded to the traditional arguments by historian and orientalists who were sceptical of the historical authenticity of hadith narrative and tradition.]